(untitled) (Community Based Medical Journal, 2026)
Laparoscopic cholecystectomy is the gold standard for gallbladder disease, but the decision to switch to open surgery is still a critical one. The purpose of the study was to determine the conversion rate, to identify predictive risk factors and to analyze the results of the institution-wide conversion rate. A retrospective cohort study was conducted in the Department of Surgery, Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, between January 2020 and December of 2022, to assess factors leading to the change from laparoscopic to open cholecystectomy and analyze the impact of early change on patient safety and post-operative outcomes. Medical records of 320 patients, who had a laparoscopic cholecystectomy course for symptomatic gallbladder disease. Demographics, pre-operative findings, operative details and post-operative results were collected. Conversion from laparoscopic cholecystectomy to open cholecystectomy rate was 4.7% (n=15). Bivariate analysis revealed age at surgery (p=0.001), particularly age 50-59 years (20.8% change), gender (19.1% vs. 2.2%, p=0.002), and history of upper abdominal surgery (26.7% vs. 3.6%, p=0.008). A slight positive correlation between age (r=0.42) and gender (r=0.36) was confirmed by Pearson correlation. The main causes of change were thickened adhesions (40%) and acute inflammations (33.3%). The converted group had significantly more time to return to activity (92.5±18.3 vs. 54.2±12.5 minutes, p=0.001) and more hospital stays (5.8±1.6 vs 2.3±0.8 days, p=0.001). The patient profile for transfer from laparoscopic cholecystectomy to open cholecystectomy was clear for high-risk patients. We observed that time-oriented transformation guided by pre-operative risk factors and intra-operative challenges are key surgical judgement that reduces the risk of major complications and prioritises patient safety in favour of procedural rigour. CBMJ 2026 January: vol. 15 no. 01 P:127-133